Psikoedukasi Tentang Pola Asuh Efektif di Masa Kini - Fadhel Muhammad Rizal; Nur Hanifah Firdaus; Nurul Auliah As Fataillah; A Maulia Fitri; Irdianti Irdianti; Uswatun Hasanah (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2022)
In the present, parents must choose an effective parenting pattern so that children avoid deviant behavior. This psychoeducational program explains the parenting pattern of parents who have children in the city of Makassar. The implementation method in this service activity is carried out offline through the provision of materials and sharing experiences. The participants in this activity are 10 subjects who had children. Activities were evaluated using the pre-test and post-test measurement models. Based on the results of the analysis using the Paired Sample T-Test, it was found that there was an increase, namely the results of the pre-test < post-test or 75,00 < 93,00. It can be concluded that this activity illustrates